Cost-effective sol-gel synthesis of porous CuO nanoparticle aggregates with tunable specific surface area - Lars Dörner (Nature Portfolio, 2019)
Abstract CuO nanoparticles (NPs) are applied in various key technologies, such as catalysis, energy conversion, printable electronics and nanojoining. In this study, an economic, green and easy-scalable sol-gel synthesis method was adopted to produce submicron-sized nanoporous CuO NP aggregates with a specific surface area > 18 m²/g. To this end, a copper-carbonate containing precursor was precipitated from a mixed solution of copper acetate and ammonia carbonate and subsequently calcinated at T ≥ 250 °C. The thus obtained CuO nanopowder is composed of weakly-bounded agglomerates, which are constituted of aggregated CuO NPs with a tunable size in the range of 100–140 nm. The CuO aggregates, in turn, are composed of equi-axed primary crystallites with a tunable crystallite size in the range of 20–40 nm. The size and shape of the primary CuO crystallites, as well as the nanoporosity of their fused CuO aggregates, can be tuned by controlled variation of the degree of supersaturation of the solution via the pH and the carbonate concentration. The synthesized submicron-sized CuO aggregates can be more easily and safely processed in the form of a solution, dispersion or paste than individual NPs, while still offering the same enhanced reactivity due to their nanoporous architecture.